PERBEDAAN TINGKAT DEPRESI PADA MURID YANG AKTIF DAN TIDAK AKTIF BEROLAHRAGA DI KELAS II SMA AL-ISLAM I SURAKARTA TAHUN 2009 - 2010 - PUTRA , ANDI PRADANA (2010)

(untitled)
Depression is a mental disturbance with pedagogical components, like sad, upset, useless feeling, failure, losing, hopeless, frustrated, and pathologic remorse, and the somatic component : anorexia, constipation, clumsy skin (feeling cold), little decline in blood pressure and pulse. The prevalence of major depression is that for woman is twice great than man. In such time, it is estimated that 5% - 6% of the population are with depression (time prevalence) and 10% of population have been in depression during their life (long life prevalence). Sport can be enjoyed by any people in the world, without considering the stratification or something related to one’s richness or poorness. Sport or other physical activity keeps not only body’s condition, but also repairs mental condition. The research aims to examine the difference of depression level on active and inactive in having sport on the second year students of Al-Islam I Senior High School Surakarta year of 2009 - 2010. The research is conducted in Al-Islam I Senior High School. The design used is descriptive analytic using cross sectional. Sample of the research is eighty respondents. To analyze the hypothesis, it is used Chi-Square test. It is found that the score of X2 count is 8,584. This score is greater than X2 table in significance level of 5% is 3,841. Due to X2 count > X2 table (8,584 > 3,841) and P value (0,033 < 0,05) thus the hypothesis H1 is accepted in which it can be concluded that there is difference of depression level on active and inactive in having sport on the second year students of Al-Islam I Senior High School Surakarta year of 2009 - 2010.